The 40S ribosomal subunit recycling complex modulates mitochondrial dynamics and endoplasmic reticulum - mitochondria tethering at mitochondrial fission/fusion hotspots - Tahmasebinia, Foozhan; Tang, Yinglu; Tang, Rushi; Zhang, Yi; Bonderer, Will; de Oliveira, Maisa; Laboret, Bretton; Chen, Songjie; Jian, Ruiqi; Jiang, Lihua; Snyder, Michael; Chen, Chun-Hong; et al. (Nature communications, 2025)
The 40S ribosomal subunit recycling pathway is an integral link in the cellular quality control network, occurring after translational errors have been corrected by the ribosome-associated quality control (RQC) machinery. Despite our understanding of its role, the impact of translation quality control on cellular metabolism remains poorly understood. Here, we reveal a conserved role of the 40S ribosomal subunit recycling (USP10-G3BP1) complex in regulating mitochondrial dynamics and function. The complex binds to fission-fusion proteins located at mitochondrial hotspots, regulating the functional assembly of endoplasmic reticulum-mitochondria contact sites (ERMCSs). Furthermore, it alters the activity of mTORC1/2 pathways, suggesting a link between quality control and energy fluctuations. Effective communication is essential for resolving proteostasis-related stresses. Our study illustrates that the USP10-G3BP1 complex acts as a hub that interacts with various pathways to adapt to environmental stimuli promptly. It advances our molecular understanding of RQC regulation and helps explain the pathogenesis of human proteostasis and mitochondrial dysfunction diseases. Coordinating protein translation with energy supply is a significant challenge faced by cells. Here, the authors found that the protein quality control network may provide a link between the two.